European Research Infrastructures - Tadić, Marko (2010)
What is exactly Research Infrastructure? How can language technologies serve as research infrastructure in humanities and social sciences? Why is the development of H-BLARK (Humanities Basic LAnguage Resources Kit) necessary for each language?
Projekt MZOS
ENG